Strategi Pengurangan Sampah Plastik di Laut Pada Kawasan Konservasi Perairan Nusa Penida : Studi Kasus Pulau Nusa Lembongan - Wiantara, I Kadek Yogi; Hendrawan, I Gede; Widiastuti, Widiastuti (Journal of Marine Research and Technology, 2021)
Coastal and marine areas on small islands have a higher vulnerability to the impact of plastic waste, where plastic is a material that is difficult to decompose. Nusa Lembongan Island is one of the small islands that is included in the Marine Protected Area (MPA) and is one of the world's marine tourism destinations with various tourism activities in it. Tourism activities have a large enough opportunity for plastic waste pollution in the environment. This study aims to develop a priority strategy for reducing plastic waste based on the approach of internal and external factors on the island of Nusa Lembongan using the analysis of Strengths, Weaknesses, Opportunities, Threats (SWOT), and Analytical Hierarchy Process (AHP). Data were collected by observation, literature study, interviews, and questionnaires. Respondents were determined by purposive sampling and snowball sampling. The results of the data obtained were analyzed using the SWOT method which resulted in alternative strategies which were then analyzed using the AHP method. The results of the study indicate that the priority strategy is to maximize environmental facilities and add segregated waste bins to create mutually beneficial relationships with groups of self-management services and to realize the prevention of the use of single-use plastic waste as stated in Pergub Bali no. 97 of 2018 take advantage of the support of local NGOs to carry out synergistic and sustainable socialization.